Crisis Communication and Conflict Resolution (1st edition) - POP-FLANJA, Delia (Presa Universitară Clujeană, 2021)
Whereas studies on communication in crisis contexts are numerous and substantial (among the most prominent - Benoit, 1995; Witte, 2001, and Coombs, 2006), the current COVID-19 health crisis has caused a disruption of classical interpretative templates, and a reconsideration of the way in which the communication strategies of different actors are applied and interpreted is necessary.